2020
DOI: 10.1007/s11332-020-00677-9
|View full text |Cite
|
Sign up to set email alerts
|

Athletes and adversities: athletic identity and emotional regulation in time of COVID-19

Abstract: Background The COVID-19 pandemic impacted on the sporting field, with athletes constrained in home isolation without the possibility to train and compete in their usual environments. This situation has been investigated within the theoretical frameworks of athletic identity and cognitive emotion regulation. Objectives The objectives of our investigation were to: (a) validate the athletic identity measurement scale (AIMS) for use in Italian language; and (b) explore differences by gender, typology of sport (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 26 publications
3
62
2
2
Order By: Relevance
“…Our results seem to be contradictory with previous studies that show lower anxiety and perceived stress among elite athletes during the COVID-19 crisis compared to either the general population or non-elite competitive athletes (Clemente-Suárez et al, 2020;Costa et al, 2020;di Fronso et al, 2020). However, in the present study, the measure of anxiety was contextualized to return to sport.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results seem to be contradictory with previous studies that show lower anxiety and perceived stress among elite athletes during the COVID-19 crisis compared to either the general population or non-elite competitive athletes (Clemente-Suárez et al, 2020;Costa et al, 2020;di Fronso et al, 2020). However, in the present study, the measure of anxiety was contextualized to return to sport.…”
Section: Resultscontrasting
confidence: 99%
“…A study on perceived stress in Italian athletes showed that male athletes and elite athletes (i.e., competing at the national and/or international level) displayed lower perceived stress during the COVID-19 lockdown than female and non-elite athletes, respectively (di Fronso et al, 2020). Additionally, Clemente-Suárez et al (2020) found lower rates of anxiety in Olympic and Paralympic athletes than in the general population, suggesting that athletes may have more cognitive and emotional resources to face the confinement situation (Costa et al, 2020). Furthermore, in a qualitative study investigating psychological correlates of return to competition in basketball players, participants stated that participation in training programs prior to returning to sport increased their confidence in having better performance and lower fear of reinjury, and that reaching their pre-injury levels of performance was the main motivation to give "100% effort" in training programs before returning to competition (Conti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these coaches may have worked with athletes who were able to continue their training also during lockdown, due to the organizational instrumental support ( Fletcher and Arnold, 2017 ). On the other hand, instead, non-elite coaches may have been working with athletes who divested from their athletic role ( Costa et al, 2020 ). Finally, due to their highly competitive working conditions and environment, elite coaches may have developed the ability to effectively and positively cope with high stressful situations ( Mellalieu et al, 2009 ; Fletcher and Scott, 2010 ; Olusoga et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, major national and international sporting competitions were suspended or postponed for 1 year ( Corsini et al, 2020 ; Gallego et al, 2020 ; Schinke et al, 2020 ). In addition to its large-scale impact on competition, the COVID-19 lockdown also impacted athletes, coaches, and supporting staff, who were kept away from their usual working (and social) environments ( Costa et al, 2020 ; Di Fronso et al, 2020 ; Jukic et al, 2020 ). In addition to limiting their ability to compete in the current season and to prepare for the next, these restrained living conditions and consequential forced physical isolation, may also have negatively impacted the psychological wellbeing of athletes, coaches and supporting staff.…”
Section: Introductionmentioning
confidence: 99%
“…Athletic identity will be the lowest in athletes who experience no change in motivation due to less rumination (see Costa et al, 2020 ). Trait anxiety is assumed to be the lowest in athletes who experience no change in motivation (see approach and avoidance temperament).…”
Section: Introductionmentioning
confidence: 99%